Determining the Coefficient of Restitution Through the “Bouncing Ball” Experiment using Phyphox - Jesi Pebralia (Universitas Sanata Dharma, 2022)
This study aims to determine the restitution coefficient based on the reflected sound from the “bouncing ball” experiment. The experiment used a Phyphox-based smartphone. The produced sound came from a reflection between marble and the floor. Theoretically, the value of the coefficient of restitution is obtained based on the square root of the final height of the object’s reflection divided by its initial height. In this study, the determination of the height of the bounce from the “bouncing ball” was measured using the Phyphox application, which was analyzed based on the sound of the bouncing ball and the time interval of the reflection. The results show that the value of the coefficient of restitution for each marble was 0.93, 0.92, and 0.92, while the average error was 0.65%, 0.85%, and 1.43%, respectively. Furthermore, the average error value of the overall measurement is 0.97%. This error is highly dependent on the shape of the object. The rounder a thing is, the higher the level of accuracy will be. In this study, the determination of the coefficient of restitution was carried out in two ways: by comparing the height of the ball’s bounce and the time intervals for the n and n+1 bounce. The value of the coefficient of restitution generated by these methods was identic. Thus, this study had confirmed that the bounce ball experiment using the Phyphox indicated valid data well so that it could be implemented for determining the coefficient of restitution.Keywords: Bouncing ball, Coefficient of restitution, Phyphox, Smartphone